Women's Agency in Action: Higher Education and Career Paths for Young Muslim Women in Indonesia - Aisyah, Siti Nur (Muslim Education Review, 2022)
This article is an analysis of narratives of young Indonesian Muslim women to explore their behavior and thoughts on being well-educated women in their chosen career path. It examines women’s thoughts on completing higher education and their lifelong study; whether pursuing a career or being a full-time mom. Having the capability to choose the career they want and implementing the beliefs of Islam’s teaching are attributed as their main responsibilities for being a real woman in this world and hereafter. The biographical interpretive method is engaged in this study to more deeply explain and explore the main idea selected. The research findings show that higher education allows women to become a new version of themselves. Obviously it can be said that education is the key for the next, better, future generations of Indonesia.